Bibliometric Analysis: Waste Reduction Strategy of Higher Education Institutions in Achieving an Environmentally Friendly Campus/Achieving a Sustainable Campus - Rina, Nur Fitrianah; Said, Abdullah; Hayat, Ainul (Graduate School Universitas Brawijaya, 2026)
Global waste production reaches 2.01 billion tons per year, with a projected increase of 70% by 2050. Universities contribute significantly, with an average of 1.5 to 2 kg of waste per student per day. Although UI GreenMetric determines that waste management contributes 18% of campus sustainability assessments, only 15% of universities in developing countries have an integrated waste management system. This study aims to identify global research patterns and trends on waste reduction strategies in higher education, analyze key thematic clusters and research gaps, and evaluate collaborative relationships between countries and institutions in sustainable campus development. A bibliometric analysis was conducted using data from the Scopus database, which encompassed 1,573 documents from 701 sources and involved 4,552 authors. Data were analyzed using Bibliometrix software in R with a quantitative approach to identify publication trends, keywords, affiliations, and research collaborations. Inclusion criteria included articles with search strings related to sustainable campuses. The validity of the method was confirmed through comparison with similar bibliometric studies and expert consultation. Research on campus waste reduction strategies revealed an annual growth rate of 5.57%, with a notable increase after 2019. The analysis identified three main clusters: higher education and management aspects; energy and campus facilities; and stakeholders and academic outputs. The distribution of research was uneven geographically, with significant contributions from Malaysia and Indonesia (each with three universities in the top 10 institutions), while international collaboration remained low (16.47%). Although research on sustainable campuses is growing rapidly, the specific aspect of waste management has not been sufficiently emphasized. This gap represents an opportunity for future research and increased international collaboration. Integrating a circular economy approach with behavioral change theory in the context of higher education has the potential to make a significant contribution to realizing a sustainable, green campus. Keywords: Sustainable Campus, Waste Management, Bibliometric Analysis, Circular Economy, Higher Education